PENGARUH UPAH MINIMUM, TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA DAN KESEJAHTERAAN MASYARAKAT - Mahendra, Sudarsana Arka, Siwa Nata (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The Government of Province Bali to expand employment opportunities and create community welfare is carried out by increasing development in the field of education and human resources to prosper and improve people's lives in various aspects towards a better life now and in the future. The purpose of this study is; 1) to analyze the effect of minimum wages and education levels on employment in regencies / cities in Bali Province; 2) to analyze the effect of the minimum wage, education level and labor absorption on the welfare of the community in Bali's regencies / cities; 3) to analyze labor absorption mediating the effect of minimum wages and education levels on the welfare of the community in the districts / cities of the Province of Bali. Data collection techniques with direct recording in the form of minimum wage data, education level, employment and public welfare in the 2014-2018 period. The data analysis technique used in this study is path analysis. The results showed the minimum wage and education level had a positive and significant effect on employment in regencies / cities in Bali Province in 2014-2018. Minimum wages, education levels and employment have a positive and significant effect on community welfare in districts / cities in Bali Province in 2014-2018. Absorption of labor mediates the effect of minimum wages and education levels on community welfare in districts / cities in Bali Province in 2014-2018.